Preferential trade agreements between the monetary community of Central Africa and the European Union: Stumbling or building blocks? A general equilibrium approach - Ngeleza, Guyslain K.; Muhammad, Andrew (International Food Policy Research Institute, 2009)
This paper uses a computable general equilibrium approach to simulate two opposing views describing regional trade agreements either as building blocks for or stumbling blocks to multilateral trade liberalization. This study focuses on the free trade agreement (FTA) between the Economic and Monetary Community of Central Africa (CEMAC) and the European Union (EU). Results show that although a regional trade agreement may slightly raise welfare among the members of the agreement, the cost to nonmembers can be high. In this paper we argue that multilateral liberalization and a regional free trade agreement between the EU and CEMAC are not mutually exclusive. Regional trade agreements should be complementary and consistent with a multilateral agreement, not an attempt to replace it. The regional breakdown in our design considers 14 regions, allowing for country-specific analysis for one least-developed country (Democratic Republic of Congo) and one non-least-developed country (Cameroon). Multilateral liberalization amplifies welfare gain for Cameroon. The Democratic Republic of Congo, with its weaker institutional capacity, is affected negatively. An EU-CEMAC FTA without multilateralism produces gains for both Cameroon and the Democratic Republic of Congo. The gain for Cameroon is, however, moderate compared with that achieved when the EU-CEMAC FTA is accompanied with a multilateral agreement.